A novel crystallizable low band gap polymer for high‐efficiency polymer photovoltaic cells. Issue 1 (13th October 2015) - Zhao, Xiaoli; Lv, Hongying; Yang, Dalei; Li, Zidong; Chen, Zhaobin; Yang, Xiaoniu
Abstract : A new crystallizable low band gap conjugated copolymer BTT‐DTFFBT is designed and synthesized. The polymer solar cells based on BTT‐DTFFBT: PC71 BM photoactive layer are fabricated and characterized. It is found that after combined treatment of 1 vol % 1‐chloronaphthalene (CN) additive and thermal annealing at 180 °C for 10 min, the device shows a power conversion efficiency (PCE) of 5.61% and good thermal stability.